Associations between signs and symptoms of dry eye disease: a systematic review - Bartlett JD (Dove Medical Press, 2015)
Jimmy D Bartlett,1 Michael S Keith,2 Lavanya Sudharshan,3 Sonya J Snedecor3 1Department of Optometry, School of Optometry, The University of Alabama at Birmingham, Birmingham, AL, 2Global Health Economics, Outcomes Research, and Epidemiology Department, Research and Development Division, Shire, Wayne, PA, 3Pharmerit International, Bethesda, MD, USA Purpose: The accurate diagnosis and classification of dry eye disease (DED) is challenging owing to wide variations in symptoms and lack of a single reliable clinical assessment. In addition, changes and severity of clinical signs often do not correspond to patient-reported symptoms. To better understand the inconsistencies observed between signs and symptoms, we conducted a systematic literature review to evaluate published studies reporting associations between patient-reported symptoms and clinical signs of DED.Methods: PubMed and Embase were searched for English-language articles on the association between clinical signs and symptoms of DED up to February 2014 (no lower limit was set).Results: Thirty-four articles were identified that assessed associations between signs and symptoms, among which 33 unique studies were reported. These included 175 individual sign–symptom association analyses. Statistical significance was reported for associations between sign and symptom measures in 21 of 33 (64%) studies, but for only 42 of 175 (24%) individual analyses. Of 175 individual analyses, 148 reported correlation coefficients, of which the majority (129/148; 87%) were between –0.4 and 0.4, indicating low-to-moderate correlation. Of all individual analyses that demonstrated a statistically significant association, one-half (56%) of reported correlation coefficients were in this range. No clear trends were observed in relation to the strength of associations relative to study size, statistical methods, or study region, although results from three studies did suggest that disease severity may be a factor.Conclusion: Associations between DED signs and symptoms are low and inconsistent, which may have implications for monitoring the response to treatment, both in the clinic and in clinical trials. Further studies to increase understanding of the etiopathogenesis of DED and to identify the most reliable and relevant measures of disease are needed to enhance clinical assessment of DED and the measurement of response to therapeutic interventions. Keywords: associations, correlations, dry eye disease, signs, symptoms, systematic literature review